Strategy for Developing Bottom-Linked Governance in the ‘GEMILANG’ Waste Bank Program Planning - Yakub, Anggelo Ibrahim (Prospect: Jurnal Pemberdayaan Masyarakat, 2025)
Environmental and institutional challenges in the Dara Sub-District, Bima City, constitute a pressing issue that requires immediate attention, as they have the potential to exacerbate environmental pollution and degrade the quality of life for its communities. The socio-ecological conditions of the area are compounded by low public awareness of waste management, a scarcity of adequate facilities, and the diminished efficacy of local institutions. In response to these challenges, PT Pertamina Patra Niaga - Integrated Terminal (IT) Bima, in collaboration with the Dara Sub-district Government and its community, has designed the GEMILANG (Gerakan Milah Sampah Lingkungan) Waste Bank Program as a community-based solution. The program's design is predicated on an Adaptive Governance Approach, which emphasizes active community participation, multi-stakeholder synergy, and governance flexibility. This approach is operationalized through: the establishment of an adaptive and polycentric institutional structure; transparent decision-making mechanisms; a continuous, multi-level cycle of social learning; and comprehensive strategies for multi-stakeholder engagement. Consequently, this model positions the GEMILANG Waste Bank Program not merely as a technical solution for waste management, but as a community empowerment ecosystem, designed to strengthen social institutions, foster innovation, and enhance the community's capacity to achieve sustainable development.